1977
DOI: 10.1182/blood.v49.5.835.bloodjournal495835
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil colony formation in semisolid cultures of human bone marrow cells

Abstract: A method for in situ staining and scoring of eosinophil colonies and clusters in the whole culture dish has been developed for agar cultures of human marrow cells. Cultures stimulated by human placental conditioned medium were found to develop the same proportion of eosinophil, neutrophil, and monocyte colonies as cultures stimulated by conventional peripheral white cell underlayers. Eosinophil colonies and clusters always contained pure populations of eosinophils, and no mixed colonies of eosinophils with oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1981
1981
1981
1981

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Conversely, colonies initiated by CSFP degenerated during the second week of culture and this fate was not significantly influenced by substituting CSFas the stimulus. Previous studies (Dresch et al, 1979;Johnson et al, 1977) indicated that these subsets of GM progenitors could be partially separated on the basis of different sedimentation velocities and the present studies documented that a similar partial segregation could be achieved by FACS separation using the fact that day 7 colony-forming cells bound more fucose-binding protein than day 14 colonyforming cells. Unfortunately only a few eosino-phi1 clusters were transferred.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Conversely, colonies initiated by CSFP degenerated during the second week of culture and this fate was not significantly influenced by substituting CSFas the stimulus. Previous studies (Dresch et al, 1979;Johnson et al, 1977) indicated that these subsets of GM progenitors could be partially separated on the basis of different sedimentation velocities and the present studies documented that a similar partial segregation could be achieved by FACS separation using the fact that day 7 colony-forming cells bound more fucose-binding protein than day 14 colonyforming cells. Unfortunately only a few eosino-phi1 clusters were transferred.…”
Section: Discussionsupporting
confidence: 76%
“…There is a heterogeneity in the physical characteristics of human colony-forming cells stimulated by human placental-conditioned medium based on whether they produce granulocyte, macrophage, mixed granulocyte-macrophage, or eosinophil colonies (Dresch et al, 1977). There are also two types of colonyforming cells based on velocity sedimentation studies.…”
mentioning
confidence: 99%